EFEKTIVAS KURIKULUM MERDEKA DALAM PROSES PEMBELAJARAN PADA SISWA SMA NEGERI 1 SOA - Maria Oktavia Dede Rua (Jurnal Ilmiah Mandalika Education (MADU), 2024)
Effectiveness has a very important role in the learning process. Effectiveness in this context refers to the level of achievement that indicates success. Of course, the implementation of this independent curriculum will not necessarily run smoothly because it is still relatively new and requires several guidelines or directions as well as preparation from teachers and schools. The aim of this research was to find out to what extent and whether the implementation of the independent curriculum during the learning process was effective at the high school level at SMA Negeri 1 Soa. The method used in this research is a qualitative method with a literature study approach. The results of this research include that this curriculum has varying impacts depending on the implementation in each school and the expertise of each educator, learning outcomes and student participation appear to have increased positively in the majority of cases. By understanding the effectiveness of this curriculum, efforts can be made to continually improve and adapt learning approaches to achieve better outcomes for students at the secondary school level.